2006
DOI: 10.1197/jamia.m2142
|View full text |Cite
|
Sign up to set email alerts
|

Design and Implementation of an Application and Associated Services to Support Interdisciplinary Medication Reconciliation Efforts at an Integrated Healthcare Delivery Network

Abstract: Confusion about patients' medication regimens during the hospital admission and discharge process accounts for many preventable and serious medication errors. Many organizations have begun to redesign their clinical processes to address this patient safety concern. Partners HealthCare, an integrated delivery network in Boston, Massachusetts, has answered this interdisciplinary challenge by leveraging its multiple outpatient electronic medical records (EMR) and inpatient computerized provider order entry (CPOE)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(57 citation statements)
references
References 17 publications
1
56
0
Order By: Relevance
“…Lastly, because both study sites utilize PAML-building software in their EMRs the error rates may be lower than in other hospitals. 35 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, because both study sites utilize PAML-building software in their EMRs the error rates may be lower than in other hospitals. 35 …”
Section: Discussionmentioning
confidence: 99%
“…20 Scores range from 0-36 and were categorized as adequate (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36), marginal (17)(18)(19)(20)(21)(22), or inadequate health literacy (0-16). We treated health literacy as a dichotomous variable in our analyses (inadequate/ marginal vs. adequate).…”
Section: Patient-related Measuresmentioning
confidence: 99%
“…[1][2][3] The inpatient setting, in particular, is the context where reconciliation has usually been described. Through the process of medication reconciliation, health care providers can improve patient care by reducing adverse drug events and medication errors (by conflict or unintentional omission) that account for $3.5 billion in hospital costs each year.…”
mentioning
confidence: 99%
“…Festinger (1957) states: "[t]he resistance to change would be a function of the satisfaction obtained from the present behaviour" (p.26). Poon et al (2006) observed that the use of non-interoperable HIT systems was likely to negatively impact workflow and productivity.…”
Section: Perceived Dissatisfactionmentioning
confidence: 99%
“…Furthermore, Poon et al (2006) also asserted that the income of healthcare providers was directly tied to their productivity but not to their quality. Consequently, dissatisfaction with productivity and workflows is likely to cause resistance to change especially in an era of decreasing reimbursement (Poon et al, 2006).…”
Section: Perceived Dissatisfactionmentioning
confidence: 99%